2021
DOI: 10.7759/cureus.17668
|View full text |Cite
|
Sign up to set email alerts
|

Do SGLT2 Inhibitors Improve Cardio-Renal Outcomes in Patients With Type II Diabetes Mellitus: A Systematic Review

Abstract: Diabetes mellitus (DM) is associated with dreadful changes in the cardiovascular and renal systems, causing increased morbidity and mortality. Sodium-glucose cotransport-2 (SGLT2) inhibitors belong to the oral hypoglycemic group of drugs believed to reduce these events by various mechanisms in DM. We performed a systematic review to determine the effectiveness of SGLT2 inhibitors in reducing cardiovascular and renal complications and address safety concerns in participants with type 2 diabetes mellitus (T2DM).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Currently, STLT2 inhibitors listed in China include dapagliflozin, canagliflozin, and empagliflozin, among which dapagliflozin is the most widely used [16,17]. SGLT2 inhibitors, as a new type of hypoglycemic agent, not only have a good effect on blood glucose control but also have significant benefits on cardiovascular disease, cerebrovascular disease, body weight, blood pressure, blood lipid, kidney function, and other indicators [18,19]. This study compared the effect of dapagliflozin treatment on the laboratory indicators of Note: a represents P < 0:05 when compared between before and after treatment within the group, b represents P < 0:05 when compared between the two groups after treatment, and c represents P < 0:05 when compared the differences before/after treatment between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, STLT2 inhibitors listed in China include dapagliflozin, canagliflozin, and empagliflozin, among which dapagliflozin is the most widely used [16,17]. SGLT2 inhibitors, as a new type of hypoglycemic agent, not only have a good effect on blood glucose control but also have significant benefits on cardiovascular disease, cerebrovascular disease, body weight, blood pressure, blood lipid, kidney function, and other indicators [18,19]. This study compared the effect of dapagliflozin treatment on the laboratory indicators of Note: a represents P < 0:05 when compared between before and after treatment within the group, b represents P < 0:05 when compared between the two groups after treatment, and c represents P < 0:05 when compared the differences before/after treatment between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the mechanism of dapagliflozin in the treatment of cardiovascular diseases has not been fully clarified, which may include a variety of mechanisms. The initial study believed that dapagliflozin could reduce the toxicity of glucose to the heart through the hypoglycemic effect, so dapagliflozin is used more in patients with cardiovascular disease complicated by diabetes [13][14][15]. Studies suggest that dapagliflozin may increase the synthesis of the hepatic ketone body, enhance myocardial energy metabolism, and improve cardiac function.…”
Section: Computational and Mathematical Methods In Medicinementioning
confidence: 99%
“…Significant microvascular alterations cause chronic kidney disease (CKD), and it affects 43.2% of type 2 diabetic mellitus (T2DM) patients. Cardiovascular disease (CVD) is a severe complication that affects 32.2% of DM type II patients and causes mortality in 50.3% of those who die from it [ 1 ]. Data from large-scale randomized controlled trials (RCTs) using SGLT2 inhibitors have shown considerable cardiovascular and renal improvement across various subgroups in heart failure (HF) patients.…”
Section: Introductionmentioning
confidence: 99%